Supra- and infratentorial acute extradural haematoma - Upadhyay, Pankaj; Srivastav, Ashok (Indian Journal of Neurotrauma, 2007)
Simultaneous presence of posterior fosse as well as supratentorial acute extradural haematoma have extremely rare occurrence. One such case is been documented. It occurred due to road traffic accident and operated successfully. A brief review of literature is being presented.
Keywords: extradural haematoma; head injury; lateral sinus; tentorial